ANALISIS PENCEGAHAN DAN PENANGGULANGAN DARURAT KEBAKARAN DI KANTOR KESEHATAN PELABUHAN KELAS II PEKANBARU TAHUN 2020 - Mega Ratu; Endang Purnawati Rahayu; Masribut Masribut; Herniwanti Herniwanti; Nopriadi Nopriadi (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2021)
Background: The purpose of this study was to analyze fire prevention and control plans and fire emergency evacuation processes at the Port Health Office (KKP) Pekanbaru Method: The population in this study were employees in the office, the selection of informants using purposive sampling method (non-probablity), amounting to 5 people. This research is a qualitative research with in-depth interviews, observation and document review. Results: The results of this study indicate that the Ministry of Maritime Affairs and Fisheries has made some prevention efforts by identifying fire hazards, inspecting fire equipment, providing training to some employees, but the fire prevention facilities are still not found. The mitigation plans that have been carried out include the formation of an emergency response team, making fire SOPs, but the post-fire form is not yet owned by the KKP. Fire emergency evacuation is still lacking in the evacuation facilities section, there are no emergency exits and emergency stairs available, the office only provides evacuation signs and gathering points. Conclusion: The Ministry of Maritime Affairs and Fisheries has not implemented proper fire prevention efforts due to the lack of means to prevent fires. The fire management plan has been prepared quite well by the KKP. Evacuation facilities are still lacking because the important points in the evacuation process are not owned by the KKP.